Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Intensified hydrodynamic cavitation using vortex flow based cavitating device for degradation of ciprofloxacin - Patil, Pravin B.; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2022)
The present work, for the first time, establishes degradation behavior of ciprofloxacin (CIP), a widely used fluoroquinolone group of antibiotics, using vortex flow based hydro-dynamic cavitation (HC) for low to high concentrations of CIP (10 and 100 mg/L). Effect of pressure on the degradation of CIP and TOC reduction was investigated on pilot plant scale (capacity 1 m3/h). Process intensifications using aeration as well as hydrogen per-oxide (H2O2) were also investigated. While aeration did not yield any significant en-hancement, process intensification using H2O2 resulted in similar to 200% enhancement in the CIP degradation as compared to HC alone. Excellent degradations, to an extent of 79 & 95%, were achieved corresponding to high cavitational yields of 7.2 x 10-4 mg/J and 86.8 x 10-4 mg/J for CIP concentrations of 10 and 100 mg/L respectively using the process intensified approach of HC and H2O2, not reported so far for cavitating devices without moving ele-ments. The developed methodology demonstrated 4-7 times improvement in per-pass degradation and low cost with high efficiency compared to the conventional cavitation. The results clearly highlight utility of the process intensified approach using H2O2 for the degradation of CIP even at high concentrations, specifically important for pharmaceutical industries requiring zero liquid discharge norms.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Antibiotics removal; ciprofloxacin; Degradation; Oxidation; Wastewater treatment